A tropical Australian refuge for photosymbiotic benthic fauna - Richards, Zoe; Garcia, Rodrigo; Moore, G.; Fromont, J.; Kirkendale, L.; Bryce, M.; Bryce, C.; Hara, A.; Ritchie, J.; Gomez, O.; Whisson, C.; Allen, M.; et al. (SPRINGER, 2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. An anomalous El Niño-associated sea surface temperature stress event was predicted to affect tropical Australian reefs, including those in North Western Australia in the summer of 2015/2016. Thermal stress events are well known to result in widespread hard coral mortality events, but other symbiotic organisms such as soft corals, giant clams and sponges can also be affected. Here, we examine whether the 2016 thermal stress event deleteriously impacted coral reef communities in the remote Bonaparte Archipelago, central inshore Kimberley bioregion, North West Australia. Our results confirm the region experienced a thermal stress event of similar magnitude to other regional localities (i.e., southern Kimberley and Scott Reef), but contrary to those locations that experienced widespread bleaching events, we find no evidence to suggest widespread mortality events occurred among photosymbiotic organisms in the Bonaparte Archipelago. Photosymbiotic organisms in this region are assumed to be well adapted to fluctuating environmental conditions; however, in this instance, a greater magnitude of night-time cooling may have driven variability in regional susceptibility to thermal stress. The Bonaparte Archipelago is emerging as a globally significant ecological refuge for photosymbiotic benthic fauna that are threatened by cumulative anthropogenic and climate stressors in other parts of their distribution.